Analysis of the structure and metabolic function of microbial community in cigar tobacco leaves in agricultural processing stage - Zhang, Qianying; Zheng, Tianfei; Yang, Zhen; Yang, Shuanghong; Cai, Wen; Li, Pinhe; Huang, Yang; Zhang, Juan; Li, Dongliang (Frontiers in Microbiology, 2023)
The agricultural fermentation processing of cigar tobacco leaves (CTLs), including air-curing and agricultural fermentation, carried out by tobacco farmers has rarely been studied. In this study, we have investigated the microbial community in the CTLs during air-curing and agricultural fermentation by 16S rRNA and ITS gene high-throughput sequencing. The results showed that the richness of microbial communities gradually increased with the development of agricultural fermentation, which means that not all microorganisms in CTLs come from the fields where tobacco grows, but gradually accumulate into CTLs during the fermentation process. Enterobacteriaceae, Chloroplast, and Alternaria were the dominant genera in the air-cured CTLs. Aquabacterium, unclassified Burkholderiaceae, Caulobacter, Brevundimonas, and Aspergillus were the dominant genera in the agriculturally fermented CTLs. Acinetobacter, Methylobacterium, Sampaiozyma, and Plectosphaerella first significantly increased, and then significantly decreased during agricultural processing. The changes in microbial communities are mainly related to their different functions during fermentation. These results may help inspire the optimization of fermentation methods for CTLs, which is of great significance for improving the quality of Chinese CTLs.